2015
DOI: 10.1007/s10549-015-3315-5
|View full text |Cite
|
Sign up to set email alerts
|

Elevated risks of subsequent endometrial cancer development among breast cancer survivors with different hormone receptor status: a SEER analysis

Abstract: Estrogen receptor (ER)-positive breast cancer patients treated with tamoxifen are known to have an elevated risk of subsequent endometrial cancer. However, it is unclear if ER-negative patients also have a higher risk of endometrial cancer. This population-based study aims to evaluate whether breast cancer patients with distinctive ER and PR status possess differential risks in developing delayed endometrial malignancy. Data were obtained from the Surveillance, Epidemiology, and End Results program (1992–2009)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 33 publications
2
32
0
1
Order By: Relevance
“…Estrogen receptor-positive breast cancer patients treated with tamoxifen are known to have an elevated risk of subsequent uterine cancer [31]. Notably, patients with invasive breast cancer have a higher risk of developing subsequent uterine cancer, regardless of hormone receptor status [7]. Mellemkjaer et al [4] found that higher risk was noted before 1975 when tamoxifen was rarely used.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen receptor-positive breast cancer patients treated with tamoxifen are known to have an elevated risk of subsequent uterine cancer [31]. Notably, patients with invasive breast cancer have a higher risk of developing subsequent uterine cancer, regardless of hormone receptor status [7]. Mellemkjaer et al [4] found that higher risk was noted before 1975 when tamoxifen was rarely used.…”
Section: Discussionmentioning
confidence: 99%
“…Published data indicate that age as well as menopausal status at diagnosis of breast cancer are important predictors of second primaries [16,[24][25][26][27][28][29][30][31][32][33][34]. Langballe et al, who investigated the risk of second malignancies in relation to menopausal status in women with breast cancer, noted that premenopausal women had an 18% increase in risk of appearance of second malignancy and this increased risk was confined to endometrial and ovarian cancers.…”
Section: Discussionmentioning
confidence: 99%
“…application of tamoxifen. It is known that the elevated risk of subsequent cancer which developed in breast cancer survivors is related to hormonal (estrogen and progesteron) receptor status [26,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations